1994
DOI: 10.1111/j.1365-2621.1994.tb08179.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin Degradation of Pacific Whiting Surimi Proteins

Abstract: MATERL4LS & METHODSCathepsin B was the most active cysteine protease in Pacific whiting fish fillets; cathepsin L was predominant in surimi. Cathepsin L showed highest activity at SY'C in both fish fillets and surimi, indicating its function in myosin degradation during conventional heating of fillers and surimi gels. Washing during surimi processing removed cathepsin B and H but not cathepsin L. Myosin heavy chain was the primary substrate during autolysis of surimi paste and actin and myosin light chain show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 24 publications
13
125
0
2
Order By: Relevance
“…A identificação das bandas foi praticamente a mesma, com a única diferença que esses autores não separaram a troponina e a tropomiosina em suas subunidades. As figuras de SDS-PAGE apresentadas por An et al (1994) trabalhando com amostras de surimi de merluza (Merluccius productus), mostram também um perfil eletroforético muito parecido, com a diferença de que não foram observadas as bandas relativas à a-actinina e as troponinas C e I. As diferenças devem-se principalmente às diferentes concentrações do gel utilizadas, gradiente de 3,2-17,4% por Cuq et al (1995), 10% no trabalho de An et al (1994) e gradiente de 6-15% no presente trabalho.…”
Section: Eletroforese Em Sds-pageunclassified
“…A identificação das bandas foi praticamente a mesma, com a única diferença que esses autores não separaram a troponina e a tropomiosina em suas subunidades. As figuras de SDS-PAGE apresentadas por An et al (1994) trabalhando com amostras de surimi de merluza (Merluccius productus), mostram também um perfil eletroforético muito parecido, com a diferença de que não foram observadas as bandas relativas à a-actinina e as troponinas C e I. As diferenças devem-se principalmente às diferentes concentrações do gel utilizadas, gradiente de 3,2-17,4% por Cuq et al (1995), 10% no trabalho de An et al (1994) e gradiente de 6-15% no presente trabalho.…”
Section: Eletroforese Em Sds-pageunclassified
“…Evaluations were conducted as described by An et al [13]. Samples were extracted with 1% brij and were evaluated for both cathepsin L activity and protein content.…”
Section: Protease Inhibitionmentioning
confidence: 99%
“…Those two factors synergistically and detrimentally influence both the raw and cooked fillets texture of Pacific whiting. The most active cysteine proteinase in raw fillets of Pacific whiting was identified as cathepsin B while the degradation of myosin in fillets and surimi gels during conventional heating was caused by cathepsin L [13]. These proteinases impact Pacific whiting's commercial value and limit the prospective market for Pacific whiting in a fillet form.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the different types of endogenous protease, such as cathepsins [12][13][14][15][16], aspartic acid proteases [17] or serine proteinases [18,19], especially the myofibril-bound serine proteinases [20,21], led to the degradation of myofibrillar proteins in fish meat.…”
Section: Introductionmentioning
confidence: 99%